The Characteristics of Teaching Material Arabic Speaking Skills in Higher Education - Zulharby, Puti; Rasyid, Yumna; Nuruddin, Nuruddin (Jurnal Al Bayan : Jurnal Jurusan Pendidikan Bahasa Arab, 2019)
Research objective is to providing an insight into the characteristics of Arabic language teaching materials in higher education in Indonesia. This research was conducted by examining a variety of literature relating to teaching materials and Arabic speaking skills. The research method applied survey, involving 97 students from the Arabic Language Education Study Program in several universities in Indonesia and structured interviews with lecturers who supported Arabic speaking skills. The procedure taken are 1) reading literature related to Arabic speaking teaching materials and teaching Arabic speaking skills, 2) observing the learning process of speaking skills at several Arabic Language Education Study Programs, 3) determining the type of survey, 4) determining the sample target, 5) preparing instruments for analyzing the needs of students, 6) preparing structured interview instruments for lecturers, 7) analyzing survey results, 8) translating survey result. The results of this study, teaching materials from Middle East has led to the emergence of gaps in achieving Arabic language skills for beginners, such as the lack of phonetic aspects being taught, monotonous forms of practice, directing students to memorize, and types of dialogue that are not in accordance with student culture in Indonesia. The characteristics of teaching materials that are suitable for use in Arabic language skills are divided into goals, phonetics, themes, social culture, exercises, steps and visualization.